Effectiveness of Loading and Unloading on the Smooth Flow of Containers at PT. Pelindo Lembar Lombok Branch, West Nusa Tenggara - Supandri, Azmi; Agus Setiono, Beni; Hidayat, Sapit (Universitas Hang Tuah, 2024)
The goal of this research is to determine the effectiveness of loading and unloading on the flow of containers at PT Pelindo Selamat Branch. This qualitative descriptive research aims to gather information about the effectiveness of loading and unloading at PT Pelindo Lembar Lombok Branch, West Nusa Tenggara. The research focuses on 3 HMC (Harbor Mobile Crane) units, 2 fixed cranes, and 2 RTG units at the PT Lembar Terminal, Pelindo Lembar Lombok Branch. The data collection methods include observation and interviews. Loading and unloading equipment, such as the Harbor Mobile Crane, play a crucial role in the stevedoring process at Lombok Terminal. However, the limited availability and frequent damage to the HMC units create obstacles in providing optimal service for users. The flow of containers at Lembar Terminal PT. PELINDO's Lombok Lembar Branch still experiences dwelling time.